Analysis of the Influence of Ticket Price Perception and Facilities on Visiting Intention at the Indonesian National Museum, Central Jakarta - Riisel Khang; Vishnuvardhana S. Soeprapto (LP2M IAIN Palopo, 2026)
The Indonesian National Museum in Central Jakarta, also known as the Elephant Museum, is one of the cultural educational tourism destinations with significant historical value in Indonesia. The number of tourist visits to this museum remains relatively low, particularly outside visits conducted by students and formal institutions. This condition is presumed to be related to the substantial increase in ticket prices as well as the suboptimal management of facilities. Purpose: This study aims to analyze the influence of ticket price perception and facilities on visiting intention at the Indonesian National Museum in Central Jakarta, both partially and simultaneously. Methods: This study employed a quantitative approach based on the positivist paradigm. The population consisted of 717,656 visitors to the Indonesian National Museum in 2025. Using the Slovin formula with a 10% margin of error, a sample of 100 respondents was selected through purposive sampling. Data were collected through observation, questionnaires using a four-point Likert scale, and documentation. The analysis techniques included descriptive statistics, validity and reliability tests, classical assumption tests, coefficient of determination analysis, partial and simultaneous hypothesis testing, and multiple linear regression analysis. Results: The findings indicate that ticket price perception has a positive and significant influence on visiting intention (t = 4.890; p = 0.000; β = 0.345). Facilities also have a positive and significant influence on visiting intention (t = 3.949; p = 0.000; β = 0.309). Simultaneously, both variables significantly affect visiting intention (F = 20.337; p = 0.000). The Adjusted R Square value of 0.281 shows that ticket price perception and facilities explain 28.1% of the variation in visiting intention, while the remaining 71.9% is influenced by other factors. Implications: The results suggest that fair ticket pricing and improved facilities can enhance visitors’ intention to visit the Indonesian National Museum. Therefore, museum management should prioritize appropriate pricing strategies and facility improvements while also strengthening promotion, destination image, and service quality.